Prince Eugene and Maria Theresa: Gender, History, and Memory in Hofmannsthal in the First World War - Wolfgang Nehring (Studies in 20th & 21st Century Literature, 2007)
Hugo von Hofmannsthal was one of the Austrian poets and intellectuals who took an active part in the historical-political events of 1914. He expected from the war a new vitality of public life and an end of the cultural crisis. In his early years he had advocated closer bonds between poesy and life. Now he encountered a situation that gave him the chance to strengthen his ties with reality. He worried about the existence of Austria, in which he was rooted, and tried to conjure up the Hapsburg spirit of the past for his contemporaries and to explain Austria's national history and right to exist to a large public. My study discusses his essay on Prince Eugene and Maria Theresa in the context of collective memory (or cultural memory) and propaganda. Is there really a collective memory? Was there a collective memory, in which the great commander and the empress lived on, or did the author wish to create this memory from history? Should his essays be considered war propaganda? Self-assertion of Austria opposite the German ally appeared almost equally important. The change in emphasis from Prince Eugene as the greatest Austrian to the peace-loving empress mirrors the events of the war. Both contribute to an Austrian anthropology, which for the author lived on beyond the end of the Empire.
Keywords: Hugo von Hofmannsthal; historical-political events of 1914; 1914; poesy; poetry; Austria; Hapsburg; Prince Eugene and Maria Theresa; collective memory; cultural memory; propaganda; war propaganda; Empire